Cause of death in adult patients with congenital heart disease: experiences of a tertiary centre. (14th October 2021) - Kecskemeti, D; Szegedi, M; Temesvari, A; Andreka, P; Balint, H
Abstract: Background: We are currently facing a growing and aging population of adults with complex congenital heart disease. However, long-term survival in these patients remained reduced. Purpose: To identify the main causes of death and compare mortality based on the complexity of the underlying congenital heart defect. Methods: Patients with at least one visit in our adult congenital heart disease (ACHD) clinic between 2010 and 2020 were reviewed. Clinical data were obtained from digital medical records. Based on the complexity of the underlying heart defect patients were classified as mild, moderate, and severe. Data about the median age at death in the general population was collected from the National Statistical Office. Survival difference between the groups was analysed using the Kaplan-Meier method along with the log rank test. Results: We included 2658 patients (53% female, overall median age of 35.6 years) with severe (21.2%), moderate (46.2%), and mild (32.6%) lesions. Over the median follow-up of 8.5 years (IQR 5.2–12.2) 125 patients (4.7%) died with an incidence of 0.51 deaths/100 patient years. The median age at death was 39.1 years (severe: 37.2 years, moderate: 50.3 years, mild: 83.1 years, p<0.001) Heart failure was the leading cause of death (35.2%) followed by non-cardiac causes (12.8%), perioperative/periprocedural death (11.2%), arrhythmia (7.4%), sudden cardiac death (4.1%) and endocarditis (2.4%). Heart failure related death was the most likely present in severely complex lesions (mild: 2.3%, moderate: 13.6%, severe: 84.1%). Underlying CHD with the highest mortality were univentricular heart (26.3%), pulmonary atresia (24.3%), Eisenmenger syndrome (22.7%), Ebstein anomaly (15.2%), and transposition of the great arteries after Senning procedure (13.4%). Conclusions: Adult patients with moderately to severely complex congenital heart disease die at a relatively young age. The highest mortality rates were observed in patients with severely complex defects, with heart failure being the most common cause of death. FUNDunding Acknowledgement: Type of funding sources: None.